Direct transmission of images along an optical fibre with the aid of spectral image encoding. - Bobrinev, VI; Son, JY; Jeon, HW (LEBEDEV PHYSICAL INST KVANTOVAYA ELEKTRONIKA JOURNAL, 1995)
An analysis is made of the possibility of using spectral encoding in parallel transmission of a two-dimensional image along a fibre.